Heavy Rainfalls and the Lunar Cycle (MAUSAM, 1965)
Heavy rainfalls during the monsoon seasons at Djakarta (1864-1945) and Mangalore (1901-1950) are found to occur more frequently at certain epochs of the lunar synodic cycle than at others. The effect is not of high statistical significance, but the results are sufficiently suggestive and in line with evidence from U.S.A. (Brier and Bradley 1964) to warrant a much more extensive study of Indian rainfall statistics. The indications that the lunar effect is much stronger in years of below average sunspot number, here and in U.S.A., may help in the elucidation of underlying processes.